Interpersonal Communication Consultation Of Doctors And Patients In The Whatsapp Media: (Study At Klinik Mitracheck) - Rafi, Muammar; Ohorella, Noviawan Rasyid; Ritonga, Aulia Rahma; Wahyuni, Sri (CONTENT: Journal of Communication Studies, 2023)
The aim of this research is to find out how interpersonal communication is carried out in doctor consultations with patients via WhatsApp media. The method used in this research uses qualitative methods. The theory used in this research is Everret M Rogers' theory of diffusion of innovation which explains that society can accept communication technology as an innovation and spread it widely within that society. The research results show that in interpersonal communication between doctors and patients via WhatsApp media, health technology is a way to make their work more efficient. Currently the world is experiencing a digital era where all human activities use information technology. Almost all fields use information and communication technology for their respective interests, one of which is the health sector. Currently, interaction between patients and doctors no longer needs to be done directly—for minor illnesses—because of information technology. In this research, the author wants to know the effectiveness of using information technology, especially WhatsApp, in the consultation process for minor illnesses between doctors and patients at the Klinik Mitracheck. The author hopes that this research can determine the effectiveness of interpersonal communication felt by patients and doctors in using WhatsApp as a consultation medium.